Alternative Position and Navigation Based on DME Accumulated Delta Range. Issue 2 (16th June 2016) - Ertan, Tunc; Psiaki, Mark L.
Abstract: A method that estimates absolute aircraft position and velocity based on time‐series of accumulated delta range measurements from distance measuring equipment (DME) ground transponders is analyzed. This method provides an Alternative Position and Navigation – but not quite Timing – system for use in airplanes as a back‐up to a Global Navigation Satellite System such as GPS. The results show that a steady‐state accuracy level better than 0.025 nm is achievable for the whole duration of a simulated flight trajectory with the tracking of four DME ground stations when aided by sporadic absolute range measurements. The system with only accumulated delta range measurements is challenged in low speed cases; however, this system exhibits convergence times of about 340 and 130 s, respectively, for an aircraft speed of 200 and 500 kn when tracking five DME ground stations. Copyright © Summer 2016 Institute of Navigation